Editorial - Dominiak, Joanna; Stachowiak, Krzysztof (Quaestiones Geographicae, 2022)
This issue of Quaestiones Geographicae is the first to be published under the supervision of new editors of the Human Geography and Spatial Management series. On behalf of the new editorial board, we would like to express our sin- cere thanks to Prof. Tadeusz Stryjakiewicz for his long-standing work as Managing Editor of the journal Quaestiones Geographicae, published by the Faculty of Human Geography and Planning together with the Faculty of Geographical and Geological Sciences of the Adam Mickiewicz University, Poznań, Poland. It is because of his commitment and effort that the journal succes- sively raised its standing in the field of geogra- phy. The volume of submitted manuscripts has been growing steadily, elevating publication standards to new levels. Today, Quaestiones Geographicae is a recognised geographical journal with a high degree of internationalisation. This achievement would not have been possible with- out the Professor’s consistent efforts. Grateful for his hard work, we are looking forward to fruit- ful collaboration with him as a member of the Editorial Advisory Board.